Social media marketing and emergence of aspirational brand luxury: Female consumers' buying behavior in Pakistan - Malik Adnan; Zahid Yousaf; Muhammad Qamar Zaman Babar; Sher Muhammad Malik (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Social media marketing has provided easy access to consumers. Luxury brands frequently keep posted their collections and proceedings on social media with the aim to save interest, engagement, create awareness as well as shape loyalties. This research is conducted in three randomly selected cities of Pakistan. The population of this research study involves all females aged 18 to 35 years and residing in Lahore, Karachi and Islamabad. A multistage random sampling technique was used; a representative sample of350 women social media users was interviewed. Results show that the most relevant factors that seem to be affecting consumer buying behavior are social media marketing. The chi-square test showed that there is anassociationbetween social media usage andbuying behavior. Regression analysis accepts the hypothesis that women buying behavior is dependent on social media marketing as well. So it is concluded that women buying behavior is influenced by social media marketing.
Keywords: 330; brand luxury; female consumer buying; women consumerbehavior; social media marketing